2018
DOI: 10.1002/anie.201804010
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Directed Iridium‐Catalyzed Hydrogen Isotope Exchange Reactions of Aliphatic Amides

Abstract: For the first time, we describe highly selective homogeneous iridium‐catalyzed hydrogen isotope exchange (HIE) of unactivated C(sp3) centers in aliphatic amides. When using the commercially available Kerr catalyst, the HIE with a series of common antibody–drug conjugate (ADC) linker side chains proceeds with high yields, high regioselectivity, and with deuterium incorporation up to 99 %. The method is fully translatable to the specific requirements of tritium chemistry and its effectiveness was demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 67 publications
1
37
0
1
Order By: Relevance
“…However, when we increased the temperature to 80 °C we observed deuteration in both positions A and B, indicating that by increasing the temperature the transitions states for both CH‐activation pathways for C(sp 2 )‐ and C(sp 3 )‐carbons are possible to be passed through. The labelling of glycine C(sp 3 )‐positions with catalyst 2 has been demonstrated earlier by us already . With catalyst 6 we obtained only traces of deuterated product due to the prior described instability of the catalyst at temperatures above 50 °C.…”
Section: Resultssupporting
confidence: 71%
“…However, when we increased the temperature to 80 °C we observed deuteration in both positions A and B, indicating that by increasing the temperature the transitions states for both CH‐activation pathways for C(sp 2 )‐ and C(sp 3 )‐carbons are possible to be passed through. The labelling of glycine C(sp 3 )‐positions with catalyst 2 has been demonstrated earlier by us already . With catalyst 6 we obtained only traces of deuterated product due to the prior described instability of the catalyst at temperatures above 50 °C.…”
Section: Resultssupporting
confidence: 71%
“…Isotopically‐labeled compounds are of prime importance for the elucidation of reaction mechanisms, as reference materials in mass‐dependent analytical chemistry and for the improvement of bioactive drugs in pharmaceutical industries . While the introduction of hydrogen isotopes into target molecules of interest had traditionally been performed by simple acid‐ or base‐mediation, the transition‐metal‐catalyzed direct activation of otherwise inert C−H bonds proved to be essential for the labeling of non‐activated target molecules, with very recent applications directed towards the late‐stage modification of drug candidates by Derdau,– Tamm, and Chirik,– among others…”
Section: Methodsmentioning
confidence: 99%
“…Pleasingly, preliminary studies from our laboratory have shown that the highly active [Ir(COD)(PPh 3 )IMes]BAr F complex 10b was effective in the sp 3 labelling of a range of morpholines, piperidines, and piperazines at low catalyst loadings and under readily accessible conditions, with the label directed by an aza‐heterocycle (Scheme 16). Some of the more challenging (acyclic) examples required a moderate increase in catalyst loading and reaction time but were, nonetheless, successfully accommodated under comparatively mild conditions. As well as a small number of open chain systems having been applied, the utility of the process was showcased by targeting active pharmaceuticals and other biological active species, including mirtazapine, azaperone, and caffeine, all of which were labelled to >90% incorporation at the sp 3 site.…”
Section: C(sp3) Labellingmentioning
confidence: 99%